STATUS HUKUM PERNIKAHAN YANG TIDAK TERCATAT MENURUT UNDANG-UNDANG PERKAWINAN INDONESIA - Elfiani, Elfiani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Registration of marriage is the administrative process relating to the registration and complete bookkeeping, to provide legal certainty about the events of the wedding. Registration of marriage is aimed to establih the rule of law in the implementation of marriage in society, so that the requirements and procedures of marriage are fullfilled as it should be. The recorded Marriage is a marriage that took place in the presence of authorized officer (Marriage Registrar Officer) ; the Religious Affairs Office (KUA) for the Moslems, and civil registry for the non-Muslims. However, a phenomenon that occurs in the community, there are many marriages that are not registered because it is done not in the presence of the Marriage Registrar Officer, and consequently no marriage certificate. Un registered Marriage is not recognized by the Indonesia Marriage Law and has no legal force.